2016
DOI: 10.3354/cr01434
|View full text |Cite
|
Sign up to set email alerts
|

Assessing freshwater life-stage vulnerability of an endangered Chinook salmon population to climate change influences on stream habitat

Abstract: tat and how species respond (Groves et al. 2012, Seney et al. 2013. Each stage of a species' life history may be affected differently by changes in its habitat. For example, Radchuk et al. (2013) ABSTRACT: We linked a set of climate, hydrology, landscape, and fish population models to estimate the relative influence of freshwater habitat variables on the abundance of a population of endangered stream-type Chinook salmon Oncorhynchus tshawytscha responding to a warming climate. The hydrology models estimated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Planting riparian vegetation and increasing connections between mainstem habitat and cooler off‐channel habitats could reduce exposure by salmon to warm temperatures (Beechie et al 2012). Several studies have suggested that riparian restoration may reduce or even ameliorate the potential effects of increased water temperature expected over the next several decades (Bond et al 2015, Sun et al 2015, Honea et al 2016, Justice et al 2017). Care will need to be taken, however, when increasing connectivity with potentially cooler off‐channel habitats to ensure that these habitats will not become ecological traps due to the presence of nonnative warmwater predators like largemouth bass.…”
Section: Discussionmentioning
confidence: 99%
“…Planting riparian vegetation and increasing connections between mainstem habitat and cooler off‐channel habitats could reduce exposure by salmon to warm temperatures (Beechie et al 2012). Several studies have suggested that riparian restoration may reduce or even ameliorate the potential effects of increased water temperature expected over the next several decades (Bond et al 2015, Sun et al 2015, Honea et al 2016, Justice et al 2017). Care will need to be taken, however, when increasing connectivity with potentially cooler off‐channel habitats to ensure that these habitats will not become ecological traps due to the presence of nonnative warmwater predators like largemouth bass.…”
Section: Discussionmentioning
confidence: 99%
“…As the NorWeST database and scenarios are periodically updated and improved, they could be used in development of spatially explicit, high‐resolution behavioral and bioenergetic models that encompass the full suite of freshwater salmon habitats and life stages (Honea et al. ; Crozier et al. ) or next‐generation species distribution models (Filipe et al.…”
Section: Discussionmentioning
confidence: 99%
“…Scenarios developed from the database provide spatially comprehensive thermal information that has contributed to an improved understanding of salmon migrations (Westley et al 2015;Palmer 2017), locations susceptible to nonnative species invasions (Al-Chokhachy et al 2016;Isaak et al 2016aIsaak et al , 2016bHowell, in press), and parameterization of distribution models that predict locations of climate refuge streams (Isaak et al 2015;Young et al 2016). As the NorWeST database and scenarios are periodically updated and improved, they could be used in development of spatially explicit, high-resolution behavioral and bioenergetic models that encompass the full suite of freshwater salmon habitats and life stages (Honea et al 2016;Crozier et al 2017) or next-generation species distribution models (Filipe et al 2017;Ver Hoef et al 2018) to further reduce remaining uncertainties and provide decision makers with ever more precise information.…”
Section: Adaptive Responsesmentioning
confidence: 99%
“…Juvenile sockeye rear in lakes for 1–3 years, but some populations utilizing streams may migrate to sea soon after emergence (Burgner, ). A consistent catch decline in coho and Chinook salmon, which have complex life history patterns requiring they spend a longer time period in rivers and streams, suggests that the decline might be mainly caused by reduced survival rates of freshwater stages adversely affected by climate change (Honea, McClure, Jorgensen, & Scheuerell, ; Springer & van Vliet, ).…”
Section: Ecological Interaction Between Wild Conspecifics and Other Smentioning
confidence: 99%